The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fonc.2021.805628
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties in the Glioma Microenvironment: Emerging Insights and Theranostic Opportunities

Abstract: Gliomas represent the most common malignant primary brain tumors, and a high-grade subset of these tumors including glioblastoma are particularly refractory to current standard-of-care therapies including maximal surgical resection and chemoradiation. The prognosis of patients with these tumors continues to be poor with existing treatments and understanding treatment failure is required. The dynamic interplay between the tumor and its microenvironment has been increasingly recognized as a key mechanism by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 165 publications
(362 reference statements)
0
11
0
Order By: Relevance
“…To further explore the correlation between FDX1 expression and clinical characteristics of glioma patients. Online tool GEPIA 9 was used to performed the survival analysis of LGG and GBM samples. The results showed that FDX1 expression was associated with overall survival (OS) and progression-free survival (PFS) in patients with low-grade glioma, but not with OS or PFS in GBM patients (Figure 4A).…”
Section: The Prognostic Value Of Fdx1 In Glioma Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the correlation between FDX1 expression and clinical characteristics of glioma patients. Online tool GEPIA 9 was used to performed the survival analysis of LGG and GBM samples. The results showed that FDX1 expression was associated with overall survival (OS) and progression-free survival (PFS) in patients with low-grade glioma, but not with OS or PFS in GBM patients (Figure 4A).…”
Section: The Prognostic Value Of Fdx1 In Glioma Patientsmentioning
confidence: 99%
“…Glioma is one of the most common central nervous system malignancies (1)(2)(3)(4)(5)(6). Evidence shows that high-grade glioma (HGG) has obvious aggressiveness and heterogeneity (7)(8)(9)(10)(11)(12)(13)(14). In 2022, the World Health Organization (WHO) updated the classification criteria of glioma according to the molecular characteristics of different gliomas, which will help patients obtain more accurate diagnoses and precise personalized treatment in clinical practice (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Differentially enriched functions between the two aging CAF score groups were analyzed to explore the underlying molecular mechanisms. We found that stroma-related functions were active in the high-aging CAF score group, including fibronectin binding, collagen binding, ECM receptor interaction, focal adhesion, and cell adhesion molecule (CAM)-related pathways, which may contribute to tumorigenesis and progression ( Walker et al, 2018 ; Winkler et al, 2020 ; Bhargav et al, 2022 ) ( Figures 4J,K ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, reports using confined compression ( 45 ) or ultrasound-based shear wave elastography ( 46 ) showed that GBM tumor tissues were stiffer than normal brain, whereas a study using shear compression reported no differences ( 47 ). Moreover, most reports agree that stiffness in the GBM tissue increases, but whether if it is ascribed to changes within the ECM, to an increased interstitial pressure, to the cells, or their combination is still under study ( 48 ). Also, numerous studies have reported the ECM stiffness to influence GBM invasion and proliferation, and to regulate cell cycle progression and proliferation through EGFR-dependent signaling and Phosphoinositide 3-Kinase (PI3K) expression ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%